The Effect of Cognitive-Behavioral Counseling on Breastfeeding Self-Efficacy of Pregnant Women - Zahra Shahsavan; Sonia Oveisi; Zinat Jourabchi (Guilan University of Medical Sciences, 2019)
Introduction: Breastfeeding has an essential role in providing maternal and infant health and as a result the society health. Breastfeeding self-efficacy is a powerful predictor of the duration of exclusive breastfeeding. Objective: This study aimed to investigate the effect of cognitive-behavioral counseling during pregnancy on breastfeeding self-efficacy of pregnant women referring to comprehensive health centers in Qazvin City, Iran. Materials and Methods: This study is a randomized controlled clinical trial conducted on 120 pregnant women referred to health centers in Qazvin City. The samples were randomly divided into intervention and control groups. The intervention group received 8 sessions of cognitive-behavioral group counseling during the third trimester of pregnancy. The breastfeeding self-efficacy Scale questionnaire was used for surveying samples before and after the intervention. For analyzing data, t-test and Chi-squared test were used. Results: The two groups were not significantly different before the intervention in terms of demographic variables. Also, the Mean±SD breastfeeding self-efficacy scores in the control (47.55±5.92) and the intervention group (47.70±7.83) were not significantly different before counseling. After the intervention, the Mean±SD breastfeeding self-efficacy score of the intervention group (57.49±5.62) was significantly higher than that of the control group (48.8±5.94) (P<0.001). Conclusion: Cognitive-behavioral counseling will increase breastfeeding self-efficacy of pregnant women. It is recommended that the results of the study be used to promote the empowerment of women in breastfeeding.